1984
DOI: 10.1111/j.1471-4159.1984.tb12858.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Stimulation of Inositol Phospholipid Turnover in Brain by Analogs of Oxotremorine

Abstract: Structural analogs of oxotremorine have been employed to examine the relationship between the binding of agonists to muscarinic receptors in guinea pig cerebral cortex and the enhancement of inositol lipid turnover. Large differences were observed in the ability of the analogs to stimulate inositol phospholipid turnover, as measured both by the increase in labeling of phosphatidate and phosphatidylinositol from 32Pi in a nerve-ending fraction, and by the stimulated release of labeled inositol phosphates from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 34 publications
(29 reference statements)
9
57
0
Order By: Relevance
“…If so, other types of metabotropic receptors linked to the I P 3 production pathway (for review, see Schoepp and Conn, 1993) should activate I CAN also. In keeping with this hypothesis and in agreement with previous data (Shen and North, 1992;Colino and Halliwell, 1993;Fraser and MacVicar, 1996), we found that activation of muscarinic receptors induced a current showing similar features to those of I CAN : under perfusion with medium A, bath application of 60 -120 M carbachol (a selective agonist of muscarinic receptors linked to IP 3 production pathway) (Fisher et al, 1983(Fisher et al, , 1984Dutar and Nicoll, 1988) generated a CAN current that was smaller but otherwise comparable to I CAN induced by 1S,3R-ACPD (n Ï­ 9; Fig. 6C, Table 1).…”
Section: Can Is Mediated By Group I Mglurssupporting
confidence: 80%
“…If so, other types of metabotropic receptors linked to the I P 3 production pathway (for review, see Schoepp and Conn, 1993) should activate I CAN also. In keeping with this hypothesis and in agreement with previous data (Shen and North, 1992;Colino and Halliwell, 1993;Fraser and MacVicar, 1996), we found that activation of muscarinic receptors induced a current showing similar features to those of I CAN : under perfusion with medium A, bath application of 60 -120 M carbachol (a selective agonist of muscarinic receptors linked to IP 3 production pathway) (Fisher et al, 1983(Fisher et al, , 1984Dutar and Nicoll, 1988) generated a CAN current that was smaller but otherwise comparable to I CAN induced by 1S,3R-ACPD (n Ï­ 9; Fig. 6C, Table 1).…”
Section: Can Is Mediated By Group I Mglurssupporting
confidence: 80%
“…The initial observations that activation of mAChRs in brain slices resulted in an increase in phosphoinositide turnover has since been amply confirmed in a variety of neural preparations, including nerve ending preparations, brain minces, and primary cultures of neurons and glia, as well as transformed cells of neural origin, such as neuroblastoma and astrocytoma (for review, see Fisher and Agranoff, 1985). Within the CNS, there exists a strong correlation between the density of mAChRs, as determined by radioligand binding techniques, and Bemdge et al (1982), Brown et al (1984), Fisher et al (1984), Gonzales and Crews (1984), Fisher and Bartus (1985), Gil and Wolfe (1989, Jacobson et al (1989, Lazareno et al (1983, Eva and Costa (1986),Heacocketal. (1987 Schoepp et al (1984), Johnson and Minneman (1985), Kendall et al (1989, Minneman andJohnson (1984) -Bush (1984-Bush ( , 1985.…”
Section: A Receptors Established To Be Coupled To Phosphoinositide Tmentioning
confidence: 99%
“…Muscarinic agonists differ considerably in their ability to enhance phosphoinositide turnover in brain. In the cerebral cortex, a group of agonists, including ACh, carbamoylcholine, and oxotremorine-M, is more effective than several others, including pilocarpine, bethanechol, and oxotremorine (Fisher et al, 1983(Fisher et al, , 1984Gonzales and Crews, 1984;Jacobson et al, 1985). The former group of agonists have been termed "group A" agonists, and the latter, "group B."…”
Section: A Receptors Established To Be Coupled To Phosphoinositide Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, whilst it is relatively easy to identify antagonists, partial agonists and full agonists it is often more difficult to distinguish differing degrees of partial agonism without detailed secondary biochemical tests e.g. phosphatidyl-inositol turnover or adenylate cyclase assays (Olianas et al, 1983;Fisher et al, 1984).…”
Section: Introductionmentioning
confidence: 99%